Developing a psychological traits scale for students of the College of Physical Education and Sports Sciences at Tikrit University - حاجمٍ, مٍ.مٍ انس حواس; Hussein, D. Imad Nasr; Ibrahim, Dr. Hamed Ahmed; Khattab, Prof. Dr. Abdul Wadood Ahmed (Sulaimani Journal for Humanities, 2026)
This study aimed to develop a psychological traits scale for students of the College of Physical Education and Sports Sciences at Tikrit University and to identify differences in the psychological traits of these students according to their academic year. The researchers hypothesized that there were no statistically significant differences in psychological traits based on academic year. The research sample consisted of 549 male and female students during the 2024-2026 academic year. The researchers used statistical methods, including percentages and correlation coefficients. Simple analysis, Spearman-Brown equation, factor analysis, one-way analysis of variance. The researchers concluded the following: The psychological traits scale was developed by the researchers based on scientific principles. The effectiveness of the psychological traits scale for students of the College of Physical Education and Sports Sciences at Tikrit University was demonstrated through the results obtained by the researchers. There are statistically significant differences in psychological trait scores among students of the College of Physical Education and Sports Sciences at Tikrit University.